Identification of risk factors for poor language outcome in surgical resection of glioma involving the arcuate fasciculus: an observational study - Fang-Ye Li; Hong-Yu Liu; Jun Zhang; Zheng-Hui Sun; Jia-Shu Zhang; Guo-Chen Sun; Xin-Guang Yu; Xiao-Lei Chen; Bai-Nan Xu (Neural Regeneration Research, 2021)
The arcuate fasciculus is a critical component of the neural substrate of human language function. Surgical resection of glioma adjacent to the arcuate fasciculus likely damages this region. In this study, we evaluated the outcome of surgical resection of glioma adjacent to the arcuate fasciculus under the guidance of magnetic resonance imaging and diffusion tensor imaging, and we aimed to identify the risk factors for postoperative linguistic deficit. In total, 54 patients with primary glioma adjacent to the arcuate fasciculus were included in this observational study. These patients comprised 38 men and 16 women (aged 43 ± 11 years). All patients underwent surgical resenction of glioma under the guidance of magnetic resonance imaging and diffusion tensor imaging. Intraoperative images were updated when necessary for further resection. The gross total resection rate of the 54 patients increased from 38.9% to 70.4% by intraoperative magnetic resonance imaging. Preoperative language function and glioma-to-arcuate fasciculus distance were associated with poor language outcome. Multivariable logistic regression analyses showed that glioma-to-arcuate fasciculus distance was the major independent risk factor for poor outcome. The cutoff point of glioma-to-arcuate fasciculus distance for poor outcome was 3.2 mm. These findings suggest that intraoperative magnetic resonance imaging combined with diffusion tensor imaging of the arcuate fasciculus can help optimize tumor resection and result in the least damage to the arcuate fasciculus. Notably, glioma-to-arcuate fasciculus distance is a key independent risk factor for poor postoperative language outcome. This study was approved by the Ethics Committee of the Chinese PLA General Hospital, China (approval No. S2014-096-01) on October 11, 2014.